Reducing Campylobacter jejuni, Enterobacteriaceae and total aerobic bacteria on transport crates for chickens by irradiation with 265-nm ultraviolet light (UV–C LED). (January 2021) - Moazzami, Madeleine; Fernström, Lise-Lotte; Hansson, Ingrid
Abstract: It is critical to maintain low levels of microbes in the whole food production chain. Due to high speed of slaughter, lack of time, and structural characteristics of crates, sufficient cleaning and disinfection of crates used for transporting chickens to abattoirs is a challenge. Inadequately cleaned transport crates for broiler chickens caused a major outbreak of campylobacteriosis in Sweden in 2016–2017, when the contaminated crates introduced Campylobacter to the chickens during thinning. This study evaluated the antibacterial efficacy of 265-nm ultraviolet (UV–C) LED light on artificially contaminated chicken transport crates. In a laboratory study, a transport crate artificially contaminated with Campylobacter and cecum contents was irradiated with 265-nm UV-C light by a continuous LED array in a treatment cabinet. The transport crate was sampled 52 times by cotton swabs before and after UV-C treatment for 1 min (20.4 mJ/cm 2 ) and 3 min (61.2 mJ/cm 2 ). The swab samples were analysed for Campylobacter jejuni (C. jejuni), bacteria belonging to the family Enterobacteriaceae, and total aerobic bacteria. After irradiation with UV-C LED light for 1 min, a mean reduction in C. jejuni of log 2.0 ± 0.5 CFU/mL was observed, while after irradiation for 3 min the reduction was log 3.1 ± 1.0 CFU/mL. The mean reduction in Enterobacteriaceae was log 1.5 ± 0.3 CFU/mL after 1 min of irradiation and log 1.8 ± 0.8 CFU/mL after 3 min. The mean reduction in total aerobic bacteria was log 1.4 ± 0.4 CFU/mL after 1 min of irradiation and log 1.6 ± 0.5 CFU/mL after 3 min. Significant reductions in bacterial load were observed in all samples after UV-C treatment and extending the treatment time from 1 to 3 min significantly increased the reduction in C. jejuni . However, before implementation of UV-C LED treatment in commercial chicken abattoirs, the irradiation unit would need to be extended and/or the washing procedure before UV-C treatment, to reduce the amount of organic matter on transport crates, would need to be improved. Highlights: 265-nm UV-C LED light had bactericidal effects on chicken transport crates. UV-C LED light reduced Campylobacter jejuni after 1 and 3 min of irradiation. Longer treatment time with UV-C light reduced Campylobacter significantly.